IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN (Studi Kasus di Madrasah Aliyah Negeri 3 Kediri) - Ngulya, Miftahul; Kurniawan, Asep (Tawazun: Jurnal Pendidikan Islam, 2019)
Educational supervision is all forms of assistance provided by school leaders to improve the ability of teachers and other personnel to achieve the goals of education. This study aims to determine the implementation of educational supervision in improving the quality of learning in MAN 3 Kediri. The method used for data collection is done by observation, interviews, and documentation, while the data analysis technique uses a descriptive qualitative research approach, which is interpreted through descriptive explanations as conclusions about supervision in improving the quality of learning. From the results of the study, it can be concluded that: Implementation of educational supervision in MAN 3 Kediri is carried out by arranging supervision programs, involving all waka, conducting upgrading through class visits, class observations, MGMP by visiting each other, training/workshops, evaluations and actions continued. In improving the quality of learning, it is carried out in collaboration with teachers in strengthening the curriculum and developing learning tools, providing learning resources, tools and various teaching and learning facilities. Implementation of educational supervision in improving the quality of learning, through guidance and curriculum development, improving teaching and learning processes, and efforts to enhance the quality of teachers through coaching and up grading. Obstacles to the implementation of educational supervision in improving the quality of learning, namely: some teachers have not been able to deliver the material well, impromptu activities, facilities and infrastructure are damaged, coaching is often done on holidays. While the supporting factors are as follows: guidance on the content and concepts of curriculum thinking, internet facilities, madrasa books, socialization, certified teachers, adequate facilities and infrastructure in carrying out teaching and learning processes. Abstrak Supervisi pendidikan merupakan segala bentuk bantuan yang diberikan oleh pemimpin sekolah kepada untuk meningkatkan kemampuan guru-guru dan personil lainnya guna mencapai tujuan dari pendidikan. Penelitian ini bertujuan untuk mengetahui implementasi supervisi pendidikan dalam meningkatkan mutu pembelajaran di MAN 3 Kediri. Metode yang digunakan untuk pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi, sementara teknik analisis datanya menggunakan pendekatan penelitian kualitatif deskriptif. Hasil dari penelitian yaitu, Implementasi supervisi pendidikan di MAN 3 Kediri dilaksanakan dengan menyusun program supervisi, dengan melibatkan semua waka, mengadakan penataran-penataran melalui kunjungan kelas, observasi kelas, MGMP dengan saling mengunjungi, pelatihan/workshop, evaluasi dan tindak lanjut. Dalam meningkatkan mutu pembelajaran, dilakukan melalui kerja sama dengan guru-guru dalam pemantapan kurikulum dan penyusunan perangkat pembelajaran, menyediakan sumber-sumber belajar, alat serta berbagai fasilitas belajar mengajar. Implementasi supervisi pendidikan dalam meningkatkan mutu pembelajaran, melalui pembinaan dan pengembangan kurikulum, meningkatkan proses belajar mengajar, dan upaya mempertinggi kualitas guru melalui pembinaan dan up grading. Hambatan Implementasi supervisi pendidikan dalam meningkatkan mutu pembelajaran yaitu: beberapa guru belum mampu menyampaikan materi dengan baik, kegiatan dadakan, sarana dan prasarana rusak, pembinaan sering dilakukan di hari libur. Sedangkan faktor pendukungnya sebagai berikut: pembinaan terhadap isi dan konsep berpikir kurikulum, fasilitas internet, buku-buku madrasah, sosialisasi, guru sudah tersertifikasi, mencukupi sarana dan prasarana dalam melaksanakan proses belajar mengajar.